2003
DOI: 10.1161/01.cir.0000097122.19430.48
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Oxidized Low-Density Lipoproteins and Angiographically Assessed Coronary Artery Disease in White Patients

Abstract: Background-Low-density lipoprotein (LDL) can be oxidatively modified by reactive oxygen species, thus generating oxLDL. The latter induce formation of specific antibodies (oxLDLAb), which are detectable in patients with atherosclerosis, in which they might play a pathogenic or a protective role. Thus, we aimed to investigate the association of antibodies with oxidized LDLs (oxLDL) (oxLDLAbs) with coronary artery disease (CAD) and acute coronary syndromes. Methods and Results-In a cross-sectional study of 529 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
1
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 45 publications
4
36
1
2
Order By: Relevance
“…In fact, our group found an inverse relation between levels of cholesterol and levels of antioxidized LDL antibodies in the general population (14). Recent studies have found no association between the levels of anti-oxidized LDL antibodies and coronary artery disease (15), and others have detected an inverse relation between IgM autoantibodies to oxidized LDL and carotid artery atherosclerosis (16).…”
mentioning
confidence: 54%
“…In fact, our group found an inverse relation between levels of cholesterol and levels of antioxidized LDL antibodies in the general population (14). Recent studies have found no association between the levels of anti-oxidized LDL antibodies and coronary artery disease (15), and others have detected an inverse relation between IgM autoantibodies to oxidized LDL and carotid artery atherosclerosis (16).…”
mentioning
confidence: 54%
“…In whites, the IgM antibody levels were positively correlated with total ( r 2 = 0.01, P = 0.03) and LDL ( r 2 = 0.017, P = 0.004) cholesterol, and cigarette smoking ( r 2 = 0.014, P = 0.007), and negatively correlated with age ( r 2 = 0.012, P = 0.02). White women with diabetes also had lower IgG antibody levels and atherosclerosis severity by different methods have yielded inconsistent results ( 6,(9)(10)(11)(12) partly because the two antibodies of oxLDL (IgM and IgG) have different mechanistic functions in the atherosclerosis pathway. While IgM antibodies inhibit macrophage uptake of oxLDL ( 13,14 ), oxLDL and IgM immune complexes induce accumulation of macrophages ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although most studies have shown a positive association of IgG OxLDL autoantibodies with CAD, particularly smaller angiographic studies (25)(26)(27), others have shown no association (28)(29)(30)(31). Several studies have also shown that IgG OxLDL autoantibodies are increased at baseline in patients with acute myocardial infarction (16,32).…”
Section: Discussionmentioning
confidence: 99%